Voluntary guidelines on the responsible governance of tenure of land, fisheries and forests in the context of national food security (FAO Rome, 2012)
Provides guidance to improve the governance of tenure of land, fisheries and forests with the overarching goal of achieving food security for all and to support the progressive realisation of the right to adequate food in the context of national food security.
Keywords: FOOD SECURITY